The Ventriloquist Illusion as a Tool to Study Multisensory Processing: An Update - Bruns, Patrick (Frontiers in Integrative Neuroscience, 2019)
Ventriloquism, the illusion that a voice appears to come from the moving mouth of a puppet rather than from the actual speaker, is one of the classic examples of multisensory processing. In the laboratory, this illusion can be reliably induced by presenting simple meaningless audiovisual stimuli with a spatial discrepancy between the auditory and visual components. Typically, the perceived location of the sound source is biased toward the location of the visual stimulus (the ventriloquism effect). The strength of the visual bias reflects the relative reliability of the visual and auditory inputs as well as prior expectations that the two stimuli originated from the same source. In addition to the ventriloquist illusion, exposure to spatially discrepant audiovisual stimuli results in a subsequent recalibration of unisensory auditory localization (the ventriloquism aftereffect). In the past years, the ventriloquism effect and aftereffect have seen a resurgence as an experimental tool to elucidate basic mechanisms of multisensory integration and learning. For example, recent studies have (a) revealed top-down influences from the reward and motor systems on cross-modal binding, (b) dissociated recalibration processes operating at different time scales, and (c) identified brain networks involved in the neuronal computations underlying multisensory integration and learning. This mini review provides a brief overview of established experimental paradigms to measure the ventriloquism effect and aftereffect before summarizing these pathbreaking new advancements. Finally, it is pointed out how the ventriloquism effect and aftereffect could be utilized to address some of the current open questions in the field of multisensory research.